DEVELOPMENT OF LOCAL POULTRY, BURGO CHICKEN TO IMPROVE FOOD SECURITY IN BENGKULU - Sutriyono, Sutriyono; Brata, Bieng; Suherman, Dadang (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
ABSTRACTThis study aims to evaluate the production, population, and develop scenarios for the development of burgo chicken. The research was conducted for 3 months in Bengkulu Tengah, Bengkulu Province. Thirty-eight respondents were selected by the snowball sampling method used in this study. Data obtained through interview. filling out questionnaires, and observing; covering the identity of respondents, rearing management, production, and population; then a population development scenario is prepared. Research result, the purpose of raising chickens for food production, business, hunting chickens, and ornamental chickens. Chickens are housed during the day and night, released during the day and night, and a combination. Egg production 6-12 eggs/hen/period, an average of 8.64 eggs/hen/period; egg laying period 2-6 times/year, average 3.14. Total egg production per year is 2946, incubated is 90.98%, egg hatchability is 80.17%; and produced 2148 chicks. The population of burgo chickens was 357 (hens 29.97%, roosters 25.21%, chicks 29.41%, and young chickens 15.41%). The highest selling value of burgo chicken is IDR 800000 (decorated chicken) and the lowest is IDR 50000. In conclusion, burgo chicken has high productivity and selling value which is able to support food security through the provision of animal food and people's purchasing power increases, and population development is slow due to poor management. Recommendations, population development by multiplying hens, improving rearing and hatchery management, increasing egg laying period, reducing mortality, and preventing predators.Â